Identification and functional analysis of a novel SMARCC2 splicing variant in a family with syndromic neurodevelopmental disorder - Ming Li; Jingqi Lin; Hongjun Fei; Jinyu Liu; Yiyao Chen; Xu Han; Yanlin Wang; Jian Wang; Renyi Hua; Shuyuan Li; Niu Li (Orphanet Journal of Rare Diseases)
Abstract Background To determine the pathogenicity of a novel splicing variant in the SMARCC2 gene identified from a pair of adult male monozygotic twins with neurodevelopmental disorder, and to investigate the genotype-phenotype characteristics associated with SMARCC2 variants. Methods Whole-exome sequencing (WES) was conducted on the proband, and candidate variants were validated using Sanger sequencing within the family. The effect of the identified splicing variant on SMARCC2 mRNA processing was analyzed using reverse transcription PCR (RT-PCR) and TA-clone sequencing using samples derived from the proband. The clinical features of the twins were collected and compared with the previously reported patients. Results The twin adult males displayed comparable phenotypes, characterized by moderate developmental delay, intellectual and language delays, dense hair, craniofacial anomalies, scoliosis, cryptorchidism, hypotonia, behavioral abnormalities, allergic purpura and eczema, and drug allergies. WES unveiled a previously unreported heterozygous splice variant of the SMARCC2 gene (NM_003075.3: c.1496 + 1G > T). Sanger sequencing confirmed that the variant was de novo in both patients. TA-clone sequencing of the RT-PCR fragments showed that the canonical splicing variant resulted in two distinct aberrant splicing events in SMARCC2 mRNA. Specifically, approximately 80% of the mutant clones resulted from the in-frame insertion of 126 bases in intron 16, while the remaining 20% showed an in-frame deletion of exon 16 (c.1383_1496del). Crystal structure analysis showed that both in-frame alterations hindered the proper formation of the alpha helix structure within the SMARCC2 protein. An analysis of genotype-phenotype correlations indicated that our patients displayed neurological phenotypes of greater severity than those observed in patients with truncating variants, instead aligning more closely with the characteristics of the missense/in-frame variant group. Conclusion We identified and reported a pair of twins suffering from syndromic neurodevelopmental disorders caused by a novel splicing variant of SMARCC2. Our findings further reinforce the notion that individuals harboring missense/in-frame variants in SMARCC2 are prone to experiencing more severe neurological phenotypes.